Implementation of the Go Green Concept in the Education System - Samar A. El-Farra; Syamsul Muqorrobin (EDUJAVARE: International Journal of Educational Research, 2023)
This research aims to conceptualize the Implementation of the Go Green Concept in the Education System. This research is a type of literature review. Data sharing with documentation from Google School about education and going green. Data analysis using Systematic Literature Review. The result of implementing the Go Green concept in the education system is a positive step to support environmental sustainability and create environmental awareness from an early age. By integrating environmentally friendly practices into daily activities in the school environment, such as using renewable energy, waste management, and planting trees, students can learn about responsibility towards the natural environment